Chemoresistance and resistance to targeted therapies in biliary tract cancer: what have we learned?. (1st February 2022) - Mayr, Christian; Kiesslich, Tobias; Modest, Dominik Paul; Stintzing, Sebastian; Ocker, Matthias; Neureiter, Daniel
ABSTRACT: Introduction: Biliary tract cancer (BTC), including intra- and extrahepatic cholangiocarcinoma and gallbladder cancer, is a rare and highly difficult to manage human malignancy. Besides late diagnosis and associated unresectability, frequently observed unresponsiveness toward and recurrence following chemotherapy or targeted therapy essentially contribute to the dismal prognosis of BTC patients. Areas covered: The review provides an update on individual mechanisms involved resistance of BTC toward conventional chemotherapy as well as targeted therapies. We review the distinct mechanisms of pharmacoresistance (MPRs) which have been defined in BTC cells on a molecular basis and examine the specific consequences for the various approaches of chemo-, targeted or immunomodulatory therapies. Expert opinion: Based on currently available experimental and clinical data, the present knowledge about these MPRs in BTCs are summarized. While some possible tactics for overcoming these mechanisms of resistance have been investigated, a BTC-specific and efficient approach based on comprehensive in vitro and in vivo experimental systems is not yet available. Additionally, a reliable monitoring of therapy-relevant cellular changes needs to be established which allows for choosing the optimal drug (combination) before and/or during pharmacological therapy.